2022
DOI: 10.1021/acsomega.1c05768
|View full text |Cite
|
Sign up to set email alerts
|

Component and Structure of Aspergillus flavipes sp.-Biodegraded Bayberry Tannins: A Potential Routine for Condensed Tannin Cleaner Degradation and Disposal

Abstract: Chemical degradation is widely used for producing lower-molecular-weight tannin compounds and tannin disposal, but it has negative effects on the environment, such as causing secondary pollution and consuming energy. For overcoming these disadvantages, a cleaner and sustainable degradation and disposal method for condensed tannins was developed through biodegradation. In this study, bayberry tannin solution, one kind of condensed tannin, was biodegraded by Aspergillus flavipes sp. at first; then, gel permeatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Hydrolysable tannins are composed of glycosidic and lipid bonds. Condensed tannins, also known as proanthocyanidins, are complex polymers with flavan-3-ol as the base structure [110]. As shown in Figure 2A, Ascacio et al [111] studied the degradation process of prune tannin and found that prune tannin belonged to a polymer of ellagic acid (ellagitannin), in which, under the action of tannase secreted by Aspergillus niger, the lipid bond was broken to form punicalin, and under the action of β-glucosidase, the glycosidic bond was cleaved from polysaccharides to form gallagic acid, and finally an ellagic acid monomer was formed.…”
Section: Glucosidasementioning
confidence: 99%
“…Hydrolysable tannins are composed of glycosidic and lipid bonds. Condensed tannins, also known as proanthocyanidins, are complex polymers with flavan-3-ol as the base structure [110]. As shown in Figure 2A, Ascacio et al [111] studied the degradation process of prune tannin and found that prune tannin belonged to a polymer of ellagic acid (ellagitannin), in which, under the action of tannase secreted by Aspergillus niger, the lipid bond was broken to form punicalin, and under the action of β-glucosidase, the glycosidic bond was cleaved from polysaccharides to form gallagic acid, and finally an ellagic acid monomer was formed.…”
Section: Glucosidasementioning
confidence: 99%